Health Literacy Status of Newly Delivered Mothers and its Related Factors; A Case Study in Esfarayen City - Ahmad Sadeghi; Hosein Rohani; Mohammad Bidkhori; Mohammadali Davari; Fateme Mohammadi vahid; Hosein Ali Bazi (Hamadan University of Medical Sciences, 2019)
Aims: The most important guarantor of maternal and fetal well-being during pregnancy is pregnancy knowledge and act on them. Health literacy is an important and modifiable factor for improving access to this awareness. The aim of this study was to determine the health literacy of newly delivered mothers and its related factors in Esfarayen city. Instruments & Methods: This cross-sectional descriptive-analytical study was carried out on 266 newly delivered mothers who referred to the health centers of Esfarayen city in 2017. The subjects were selected by stratified random sampling method. Data were collected using maternal health literacy and pregnancy outcomes questionnaires (MHLAPQ). Data were analyzed using SPSS 19 software through statistical tests including independent t-test and one-way analysis of variance. Findings: The mean score of maternal health literacy was 57.07±9.94. There was a significant relationship between maternal health literacy with educational level and occupation (p<0.001). However, there was no significant relationship between maternal health literacy with the consumption of multivitamin and ferrous sulfate supplementation and birth weight of the baby (p>0.05). Conclusion: The health literacy status in newly delivered mothers of Esfarayen city is in a favorable situation and occupation and education are the related factors with the health literacy of the newly delivered mothers.